Penerapan Pembelajaran Tematik Terpadu Menggunakan Model Kooperatif Tipe Two Stay Two Stray Di Kelas IV SDN 08 Padang Besi Kota Padang - Rozi Ratna Sari; Elfia Sukma (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
This research is motivated by the implementation of integrated thematic learning in elementary schools which is less than optimal and has not met expectations. This is because the teacher has not maximally implemented integrated thematic learning, such as not using a learning model, so that students are less active and less interested in learning which causes learning objectives not achieved. The purpose of this study was to describe integrated thematic learning using the Two Stay Two Stray (TS-TS) cooperative model in class IV SDN 08 Padang Besi, Padang City in terms of implementation steps and problems in implementing integrated thematic learning using TS-TS. This research is a qualitative descriptive study. The subjects in this study were teachers and fourth grade students of SDN 08 Padang Besi, Padang City. Data collection techniques using observation, interviews, and documentation. The data analysis technique used is descriptive analysis, namely data reduction, data presentation and conclusion drawing. The data validity technique used was the method and source triangulation technique. The results showed that the steps for implementing integrated thematic learning followed the stages using TS-TS preparation, teacher presentations, group activities, formalization, group evaluation and awards. Problems in the implementation of integrated thematic learning are students who are passive, annoy friends, lack enthusiasm, shame in expressing opinions, divided student focus, classroom management by teachers, effectiveness of time, preparation and depth of material.